The extent of the impact of disclosure transparency standards (Standard & Poor's) on the value of economic units listed on the Iraqi Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:           This research aims to know the extent to which the Iraqi economic units in the research sample apply standards of transparency of disclosure (Standard & Poor's) and reporting, as well as employing these indicators to analyze the content of the annual financial reports of the economic units in the research sample listed on the Iraqi Stock Exchange to determine the extent of their commitment to applying the indicators, as The results of the analytical research of the annual financial reports showed that the commitment of the banking sector companies, represented by the Commercial Bank of Iraq and the International Development Bank for Investment and Finance, is among the sectors (research sample) in applying standards of transparency of disclosure (Standard & Poor's), meaning that the level of commitment to disclosure requirements is indicators (Standard & Poor's) The general average for the Commercial Bank of Iraq was 77.50%, the International Development Bank for Investment and Finance was 77.18%, and the lowest level was 50.93% for Al Khatim Communications Company. In addition, the general level of compliance with disclosure requirements according to (S&P) for the economic units in the research sample constituted 64.37%, which represents an average percentage.